Associations of molecular genetic predictors of type 2 diabetes mellitus with hyperglycemia in extremely low birth weight infants - P. I. Mironov; N. N. Mingazov; R. R. Valiev; А. U. Lekmanov (Вестник анестезиологии и реаниматологии, 2021)
Hyperglycemia in premature newborns is an independent risk factor for death, so blood glucose testing is widely used in the practice of neonatal intensive care units.Objective: to evaluate the associations of the frequency of carriage of allelic variants of polymorphic loci of genes predisposing to type 2 diabetes mellitus in newborns with extremely low body weight and hyperglycemia.Methods. The study design is prospective, controlled, single – center, non-randomized. Genomic DNA samples were studied in newborn infants with extremely low body weight (ELBW) (n = 105). Previously, we compared the distribution of allele frequencies of the studied genes between a group of newborns with ELBW and a population sample of adults (control). Then, the distribution of allele frequencies of the genes was compared depending on the presence of hyperglycemia in newborns with ELBW. For the analysis, loci with already known association with the development of type 2 diabetes mellitus were selected ‒ ADRB2 (rs1042713) and (rs1042714), ADRB3 (rs4994), GNB3 (rs5443), PPARA (rs4253778), PPARD (rs2016520), TCF7L2_IVS3 (rs7903146) and TCF7L2_IVS4 (rs12255372), PPARGC1A (rs8192678), MTHFR (rs1801131), PPARG (rs1801282), MTNR1B (rs10830963), SIRT1 (rs7069102).Results. In newborns with ELBW, we found a more frequent occurrence of the mutant allele A of the polymorphic locus rs8192678 in the PPARGC1A gene and the allele C of the polymorphic locus rs4253778 in the PPARA gene, in contrast to the adult population sample. But in newborns with ELBW, hyperglycemia is most likely associated with the carrier of the allele C rs1801282 of the PPARG gene (χ2 = 18.972, p < 0.001) and the allele T rs7903146 in the TCF7L2 gene (χ2 = 11.496, p < 0.001).Conclusions. The carriage of the allele С rs1801282 of the PPARG gene is characterized by the presence of a strong conjugation with hyperglycemia in newborns with extremely low body weight. It is desirable to monitor the level of glycemia in the conditions of neonatal intensive care units, taking into account the carriage of genes predisposing to hyperglycemia.